The Juridical Impications Of Withdrawal Life-Support In Hospital in Indonesia - Isniani Ramadhani; Sekar Prabarini (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2021)
Withdrawal life-support is mainly categorized as part of euthanasia. When viewed from the aspect of criminal law in force in Indonesia, Indonesia does not permit active euthanasia by anyone (including doctors and medics). If the doctor ends the patient’s life by euthanasia is considered to violate criminal law. The study aimed to find out about life-support for patients with brainstem death in the hospital and to find out about the juridical implications of withdrawal life-support in cases of brain stem death. Based on the data discovered to be recorded, some conclusions that life support for brain stem death patients in the hospital is not needed because the element is futile. The juridical implications of withdrawal life-support in brain stem death patients in hospitals can be exempted from lawsuits if the doctor has implemented duties by medical ethics and acting in a medical professional manner, especially article 344 of The Criminal Code.